Effects of different packaging methods on microbial, chimerical and sensory properties of Nile (Tilapia Oreochromis niluticus Linnaeus, 1758) fillets during refrigerator storage - F. Mashayekhi* ; Y. Morady; A Ashraf Gohari; M. Jafar; G. Zarea; Alireza R.G. (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2013)
The effect of three different packaging methods including Modified Atmosphere Packaging (MAP), Vacuum Packaging and normal Packaging was investigated on the quality of Nile tilapia fresh fillets stored in the refrigerator's temperature. The packaged samples were examined for 10 days with regard to the changes in chemical (TVN, PV, pH), microbial (total viable count) and sensory evaluations. The results indicated that the samples packed in MAP condition had higher quality than that of other methods at the end of the storage period. In addition, the slower destructive impacts and microbial growth was observed in MAP. The results of present study suggest that packaging tilapia under MAP conditions results in the increase in the durability, storing, and distribution period for fillets.